‘They Carried the Land Itself’: Eco-Being, Eco-Trauma, and Eco-Recovery in Tim O’Brien’s The Things They Carried: English - Cochran, James (Journal of Ecohumanism, 2022)
This essay calls for a wider use of Tina Amorokâ€™s (2007) concepts of eco-Being, eco-trauma of Being, and eco-recovery of Being in ecocritical literary studies. I propose the adoption of Amorokâ€™s concepts as a literary hermeneutic because it provides a theoretical model that positions ecological damage as central to wartime trauma. To demonstrate the effectiveness of Amorokâ€™s framework, the following essay reads Tim Oâ€™Brienâ€™s 1990 novel The Things They Carried alongside Amorokâ€™s eco-Being, eco-trauma, and eco-recovery. Reading Oâ€™Brienâ€™s text through Amorokâ€™s model is particularly intriguing and noteworthy because almost no critics investigate the ecocritical dimensions of Oâ€™Brienâ€™s novel.Â Yet, despite the absence of green scholarship surrounding Oâ€™Brienâ€™s novel, Amorokâ€™s framework, as I will show, draws attention to the environmental costs of war as depicted in Oâ€™Brienâ€™s novel. Applying Amorokâ€™s model as an ecocritical lens to The Things They Carried demonstrates how we can use Amorokâ€™s tripartite structure to further unpack the ecological dimensions of fiction that seemingly have little to do with the environment.